The Pacific Rat Race to Easter Island: Tracking the Prehistoric Dispersal of Rattus exulans Using Ancient Mitochondrial Genomes - West, Katrina; Collins, Catherine; Kardailsky, Olga; Kahn, Jennifer; Hunt, Terry L.; Burley, David V.; Matisoo-Smith, Elizabeth (Frontiers in Ecology and Evolution, 2017)
The location of the immediate eastern Polynesian origin for the settlement of Easter Island (Rapa Nui), remains unclear with conflicting archaeological and linguistic evidence. Previous genetic commensal research using the Pacific rat, Rattus exulans; a species transported by humans across Remote Oceania and throughout the Polynesian Triangle, has identified broad interaction spheres across the region. However, there has been limited success in distinguishing finer-scale movements between Remote Oceanic islands as the same mitochondrial control region haplotype has been identified in the majority of ancient rat specimens. To improve molecular resolution and identify a pattern of prehistoric dispersal to Easter Island, we sequenced complete mitochondrial genomes from ancient Pacific rat specimens obtained from early archaeological contexts across West and East Polynesia. Ancient Polynesian rat haplotypes are closely related and reflect the widely supported scenario of a central East Polynesian homeland region from which eastern expansion occurred. An Easter Island and Tubuai (Austral Islands) grouping of related haplotypes suggests that both islands were established by the same colonization wave, proposed to have originated in the central homeland region before dispersing through the south-eastern corridor of East Polynesia.